Cloud infrastructures, services, and IoT systems for smart cities : second EAI International Conference, IISSC 2017 and CN4IoT 2017, Brindisi, Italy, April 20-21, 2017, Proceedings /: second EAI International Conference, IISSC 2017 and CN4IoT 2017, Brindisi, Italy, April 20-21, 2017, Proceedings. ([2018]) - Unknown
No abstract available